Working Remotely, evaluations of workers regarding advantages and disadvantages, stress perception, and quality of life - Benavides, Karla Miranda (2021)
This article presents the results of a study directed towards a group of remote workers in Costa Rica, to know their perceptions of remote work including the advantages and disadvantages, amount of stress, and effect on quality of life. Qualitative research was performed with a descriptive scope using interviews. The results of this study show people's opinions in two scenarios: the first, in normal circumstances where there is an agreement between the employer and the worker to carry out remote work, and the second, mandated by the conditions of the COVID-19 pandemic. The results obtained in the study are of interest to those responsible for making decisions related to the management of human talent, well-being and the integral health of remote workers, and provides recommendations to improve their quality of life.